Acts of pedagogical resistance: Marking out an ethical boundary against human technologies. Issue 4 (May 2021) - McNair, Lynn J; Blaisdell, Caralyn; Davis, John M; Addison, Luke J
This article highlights an action research project that sparked transformation regarding how early years practitioners documented children's learning. The dominant discourse of standardisation and narrowing of early childhood education, encapsulated in the Organisation for Economic Co-operation and Development's International Early Learning Study, has resulted in the 'shaping' and 'testing' of young children around the globe. The OECD has become very interested in early childhood education and is a very instrumental player today (Moss, 2018). Consequently, the testing of young children has been instigated by governments to ensure children gain the accepted knowledge, skills and dispositions required to be successful learners. Situated within this context of testing and standardisation, this article will share knowledge gained from a small action research project that took place in one Scottish early years setting. The study was stimulated by the early years practitioners of the setting, who strongly opposed the 'reductionist' formal 'tick-box' assessments produced by their local authority. These types of didactic formal assessments suggest that pedagogy is underpinned by a desire to tame, predict, prepare, supervise and evaluate learning. This article is of critical importance as it examines the imposition of didactic assessment from the practitioners' perspective. The practitioners in the study contested that 'tick-box' assessments diminished children's identities down to a list of judgements about their academic abilities, or lack thereof. The introduction of the 'tick-box' assessments presented a dilemma for the practitioners, in terms of the different views of the government and practitioners of what knowledge is worth knowing and what individuals and groups are able to learn. Many of the practitioners from the early childcare and learning setting positioned themselves and their work as being consciously different from what was going on in the wider sector. The early childcare and learning setting employed in this article introduced a new method to capture children's learning, which they named the 'Lived Story' approach. In this article, we argue that Lived Stories are a form of narrative assessment which are designed to track children's progress whilst respecting the complexity of their learning, their position within the learning process, the flow/fluidity of their ways of being and their ability to act in radical, creative and innovative ways. We conclude that by using 'Lived Stories' practitioners were able to lessen the surety of the language we use. The article highlights that as practitioners write Lived Stories and assess children's progress they are freed to use language such as 'wondering, puzzling, thinking, exploring'. In turn, we demonstrate that this language, and the ideas it enables, are on a continuum; a journey that spans a lifetime.